The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/pathogens9040296
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antimicrobial and Wound-Healing Activity of Resveratrol, Dihydroquercetin, and Dihydromyricetin against Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans

Abstract: An increase in the spread of antibiotic-resistant opportunistic microorganisms causes serious problems in the treatment of purulent infections, burns, and trophic ulcers. We tested the antimicrobial activity in vivo of three polyphenols, Resveratrol, Dihydroquercetin (Taxifolin), and Dihydromyricetin (Ampelopsin) from Norway spruce bark to promote the elimination of Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans from wounds. Purulent infection was modelled on wounds in rats infected with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 22 publications
(26 reference statements)
2
30
0
Order By: Relevance
“…Quercetin, rutin (a glycoside of quercetin), morin (a structural isomer of quercetin), and taxifolin (a reduced form of quercetin) were used as flavonoid components for the combinations (see Figure 1 ). These flavonoids are well-known natural antioxidants whose potential health benefits have attracted a great deal of interest in their studies as prospective drugs [ 7 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Thus, a large and growing body of literature has been devoted to the modification of their biopharmaceutical and physicochemical properties, such as antioxidant activity and bioavailability, by crystal engineering [ 40 , 41 , 42 , 43 , 44 ], obtaining solid dispersions [ 45 , 46 , 47 , 48 , 49 ], and the development of new polymorphic forms [ 50 , 51 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin, rutin (a glycoside of quercetin), morin (a structural isomer of quercetin), and taxifolin (a reduced form of quercetin) were used as flavonoid components for the combinations (see Figure 1 ). These flavonoids are well-known natural antioxidants whose potential health benefits have attracted a great deal of interest in their studies as prospective drugs [ 7 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Thus, a large and growing body of literature has been devoted to the modification of their biopharmaceutical and physicochemical properties, such as antioxidant activity and bioavailability, by crystal engineering [ 40 , 41 , 42 , 43 , 44 ], obtaining solid dispersions [ 45 , 46 , 47 , 48 , 49 ], and the development of new polymorphic forms [ 50 , 51 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Pastore et al, anti‐inflammatory and wound healing effects of resveratrol depend rather on their interaction with epidermal growth factor receptor (EGFR)‐controlled cytoplasmic and nuclear pathways than on their direct antioxidant and free radical scavenging activity 35 . An in vivo study in rats showed that resveratrol can limit the infiltration of mast cells toward the wounded area, while the infiltration of lymphocytes and macrophages is stimulated 60 . It is assumed that resveratrol is able to suppress an acute antigen‐dependent reaction (Th1‐type response) in favour of a Th2 response.…”
Section: Resveratrol In Skin Wound Healingmentioning
confidence: 99%
“…Other compounds that could be an excellent solution to prevent staphylococcal infections and bacterial resistance are phenolic compounds such as resveratrol or dihydroquercetin [ 27 , 28 , 29 ] ( Table 2 ). In particular, resveratrol is an efflux pump inhibitor that increases the efficacy of other antimicrobials [ 27 ]. However, resveratrol is an antioxidant compound [ 58 ], and therefore, its use in combination with oxidative stress-generating antimicrobials could decrease the efficacy of the anti-staphylococcal therapy [ 59 ].…”
Section: Treatments Based On Feed Supplementsmentioning
confidence: 99%
“…Feed supplements could also be based on inorganic molecules with antimicrobial activity, such as zeolites (e.g., clinoptilolite) with antimicrobial activity against S. aureus [26]. Other compounds that could be an excellent solution to prevent staphylococcal infections and bacterial resistance are phenolic compounds such as resveratrol or dihydroquercetin [27][28][29] (Table 2). In particular, resveratrol is an efflux pump inhibitor that increases the efficacy of other antimicrobials [27].…”
Section: S Aureusmentioning
confidence: 99%